Lower gastrointestinal bleeding due to pancreatic cancer: an unusual presentation - Larrosa, Camila (2023)
Pancreatic cancer is a malignant neoplasm with a poor prognosis. When it manifests clinically with cold jaundice, general repercussion or dyspepsia, it usually corresponds to a locally advanced tumor. Enterorrhagia as a form of presentation of pancreatic cancer is extremely infrequent; it corresponds to a severe form with an ominous prognosis. We present the case of a 61-year-old man who attended emergency service for enterorrhagia associated with organic abdominal pain and general repercussions, to whom a diagnosis of pancreatic tail cancer was diagnosed. Colonoscopy revealed mucosal infiltration with intense edema, erythema, necrosis, and spontaneous bleeding at the level of the splenic flexure of the colon. Histology confirmed colonic infiltration by pancreatic neoplasm. Computed tomography allowed staging in stage IV. Palliative surgical treatment was performed, with a survival of 3 months.